2007
DOI: 10.1002/pssc.200673292
|View full text |Cite
|
Sign up to set email alerts
|

Exciton spin dynamics in ZnO epilayers

Abstract: We used time-resolved optical orientation experiments to study the low temperature spin dynamics of a ZnO epilayer. The sample shows a circular polarisation of the donor-bound exciton of 11% with a decay time of 275 ps. A very narrow spectral dependence of the initial polarisation and a rapid decrease of the polarisation decay time with temperature are also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recently, Chen et al [58] pointed out that two dominating factors may limit the efficiency of optical spin detection in ZnO-based materials, which are the weak spin-orbit interactions and the fast carrier/exciton spin relaxations in ZnO. According to their analyses [58], the weak spinorbit coupling (À 3.5-16 meV [58][59][60][61][62][63][64]) leads to the cancellation of the circular polarization from the optical transitions between the conduction band and valence band states in ZnO and the spin relaxation is very fast (45-80 ps at 2 K [58]) especially when the ZnO is of high impurity density [58]. Our recent studies [65] based on time-resolved optical orientation measurements also show that the spin coherence time in ZnO is significantly decreased when the density of ''impurity'' states increases.…”
Section: Structural Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Chen et al [58] pointed out that two dominating factors may limit the efficiency of optical spin detection in ZnO-based materials, which are the weak spin-orbit interactions and the fast carrier/exciton spin relaxations in ZnO. According to their analyses [58], the weak spinorbit coupling (À 3.5-16 meV [58][59][60][61][62][63][64]) leads to the cancellation of the circular polarization from the optical transitions between the conduction band and valence band states in ZnO and the spin relaxation is very fast (45-80 ps at 2 K [58]) especially when the ZnO is of high impurity density [58]. Our recent studies [65] based on time-resolved optical orientation measurements also show that the spin coherence time in ZnO is significantly decreased when the density of ''impurity'' states increases.…”
Section: Structural Propertiesmentioning
confidence: 97%
“…These may be the possible reasons for no observation of spin polarization in our magneto-PL studies. However, some successful magneto-optical studies [60,61,[65][66][67][68][69][70][71] have also been reported, despite of the two claimed ''dominating factors'' [58]. For example, long electron spin coherence times (up to 20 ns at 30 K [66]) were observed in ''relatively clean'' undoped ZnO samples using time-resolved Faraday/Kerr rotation spectroscopy at low-temperatures [65][66][67][68], and even at elevated temperatures (188 ps at 280 K [66]); a not short hole spin coherence time (350 ps at 1.7 K) in ZnO [61] and a not small polarization (11% at 20 K [60]) together with a not short decay time (275 ps at 20 K [60]) of donor-bound exciton were observed in ZnO using time-resolved magneto-PL studies; evident free [69] and bound [70] exciton splittings were observed in ZnO-based DMS materials using magnetic-optical techniques and well explained [71].…”
Section: Structural Propertiesmentioning
confidence: 99%